A Need to Revisit Air Temperature Measurements in India in the 19th and Early 20th Centuries - Kelkar, R. R. (MAUSAM, 2025)
ABSTRACT. The paper focuses on two major transitions that the meteorological observational system in India has undergone. The first was in the late 1870s when thermometer sheds were set up at Indian observatories, and the second in the 1920s when there was a changeover from thermometer sheds to Stevenson screens. The paper expresses the need to investigate possible biases in the data and apply corrections in order to construct a more credible and homogeneous 150-year temperature record over India.